Políticas de educação e saúde para o atendimento às pessoas privadas de liberdade no Estado do Paraná: o necessário enunciado das assistências ressocializadoras - Costa, Marta Cossetin (2017)
This dissertation has as its object of investigation Health and Education Policies for the Paraná state Freedom Deprived Population. To do that we will study the Paraná State Department of Corrections Guidebook (DEPEND): Practices and Technical Guidance from Health Professionals in the Paraná State Correction Facilities (2011a); Correctional Treatment Practices in the Paraná State Correctional Facilities (2011b); Managing Practices and Administrative Procedures in the Paraná State Correctional Facilities (2011c); and Safety Practices in the Paraná State Correctional Facilities (2011d). Our general goal is to apprehend, through international, national and DEPEN (2011) guidebook rules, the guidance concerning Health and Education service offer for Paraná state Freedom Deprived Population. The research problem is: what are the guidance policies regarding Health and Education service offer for Paraná state Freedom Deprived Population in DEPEN (2011) guidebook, taking into account international and national ruling systems? We tried to solve the aforementioned problem through Documentary Research by discussing concepts that regard Health and Education service offer for Freedom Deprived Populations according to international and national ruling systems as well as DEPEN (2011) four guidebooks. Through this research results we could understand, under international and national ruling systems and DEPEN (2011) guidebooks, that the guidance regarding Health and Education services offer for Paraná state Freedom Deprived Population, as well as other Social Policies, work in order to maintain consensus and perpetuate capitalist supremacy and accumulation, besides its needing for answering to socially vulnerable groups. Therefore, Health and Education policies for Freedom Deprived Populations are focused policies, with non-global nature. They are aligned with International Organization determinations, lead by the USA, and emphasize poverty managment. DEPEN (2011) guidebooks point out to the reintegration statement for Freedom Deprived Populations through Assistance practices such as Health and Education Assistance. Paraná state law, regarding that, state Health, Education and the reintegration statement as fundamental human rights for the freedom deprived population, which does not withdraws its repressive nature.